Strategi Komunikasi Pemasaran dalam Pengembangan Pariwisata Kabupaten Blitar Pada Penggunaan Aplikasi Amazing Blitar - Meifilina, Andiwi (Jurnal Komunikasi Nusantara, 2020)
The purpose of this study is to determine the marketing communication strategy in the development of regional tourism in Blitar using the Amazing Blitar application. This study uses descriptive qualitative research method, with documentative data collection technique. The result showed that the use of STOP SIT marketing communication strategy in marketing communication strategy in the development of tourism in the Blitar in the use of Amazing Blitar application, namely Segmentation, Targeting, Objectives, Positioning, Sequence of Tools, Integrating, Tools. In the marketing communication strategy in the development of tourism in the Blitar area, the use of the Amazing Blitar application continues to be studied to determine the strengths and weaknesses of the Amazing Blitar application, identifying all opportunities and obstacles or threats faced. Marketing promotion or development programs are prepared by considering various aspects and analyzing the target market, namely tourists from both within and outside Blitar. In the STOP SIT marketing communication strategy must be a planning which is an introduction to the problem, namely an analysis of the external and internal environment which produces several main problems or weaknesses, strengths, threats and opportunities. So that in the STOP SIT analysis, it is better if you also know the problem or obstacle or strength that the company has, both in terms of human resource capabilities, technology applications, facilities, capitals, and networks.